Relationship between quadriceps muscle computed tomography measurement and motor function, muscle mass, and sarcopenia diagnosis - Mizuno, Takafumi; Matsui, Yasumoto; Tomida, Makiko; Suzuki, Yasuo; Ishizuka, Shinya; Watanabe, Tsuyoshi; Takemura, Marie; Nishita, Yukiko; Tange, Chikako; Shimokata, Hiroshi; Imagama, Shiro; Otsuka, Rei; et al. (Frontiers in Endocrinology, 2023)
Background: The quadriceps muscle is one of the human body's largest and most clinically important muscles and is evaluated using mid-thigh computed tomography (CT); however, its relationship with motor function and sarcopenia remains unclear. Herein, we investigated the relationship between the crosssectional area (CSA) of the quadriceps muscle, CT attenuation value (CTV), dual-energy X-ray absorptiometry muscle mass measurements, and muscle strength and motor function to evaluate the relationship between muscle mass loss and motor function decline, determine the diagnostic ability for sarcopenia, and confirm the usefulness of quadriceps muscle CT evaluation.Methods: A total of 472 middle-aged and older community dwellers (254 men and 218 women) aged ≥40 years (mean age: 62.3 years) were included in this study. The quantity and quality of the quadriceps muscle were assessed using CSA and CTV (CSA×CTV) as a composite index multiplied by quality and quantity. Age-adjusted partial correlations by sex with eight motor functions (knee extension muscle strength, power, normal walking speed, fast walking speed, grip strength, sit-up ability, balance ability, and reaction time) were evaluated, including correction methods for height, weight, and body mass index (BMI). Further, the accuracy of sarcopenia diagnosis was evaluated using appendicular muscle mass with dual-energy X-ray absorptiometry measurements, grip strength, and walking speed as the gold standard, and receiver operating characteristic curves were plotted to evaluate diagnostic performance.Results: In men, CSA and CSA×CTV were significantly associated with seven of the eight motor functions (p<0.05), excluding only balance ability. BMI-corrected CSA was significantly correlated with all eight motor functions in men and women (p<0.05). In the diagnosis of sarcopenia based on skeletal muscle index, CSA (area under the curve (AUC) 0.935) and CSA×CTV (AUC 0.936) and their correction by height (CSA/height (AUC 0.917) and CSA×CTV/height (AUC 0.920)) were highly accurate and useful for diagnosis in men but moderately accurate in women (CSA (AUC 0.809), CSA×CTV (AUC 0.824), CSA/height (AUC 0.799), CSA×CTV/height (AUC 0.814)).Conclusions: The present results showed that a single CT image of the quadriceps muscle at the mid-thigh is useful for diagnosing sarcopenic changes, such as loss of muscle mass, muscle weakness, and muscle function.